Arbovirological survey in Silica plateau area, Roznava District, Czechoslovakia - Hubálek, Z; Cerný, V; Mittermayer, T; Kilík, J; Halouzka, J; Juricová, Z; Kuhn, I; Bárdos, V (Journal of hygiene, epidemiology, microbiology, and immunology, 1986)
The serosurveys conducted in the Silica plateau area of the Slovak karst region revealed the presence of specific neutralizing antibody against tick-borne encephalitis (TBE) virus in 18% of local inhabitants (33 examined, mostly goats and sheep farmers), 54% of goats (26 examined), 18% of sheep (120 examined) and 13% of cattle (60 examined), against Lipovník (LIP) virus in 30% of inhabitants, 88% of goats, 55% of sheep and 45% of cattle, and against Bhanja (BHA) virus in 27% of inhabitants, 46% of goats, 29% of sheep and 23% of cattle. The results of hemagglutination-inhibition tests with TBE and BHA antigens were analogous. A detailed analysis of these serologic data points to a recent enhancement of the circulation of LIP and BHA viruses and to a very low TBE virus activity in this natural focus of arboviral infections. The immunological surveys of the 32 former "Roznava disease" patients, conducted 25 years after an extensive epidemic of a TBE virus infection that originated in Roznava in 1951, revealed the presence of neutralizing (and also hemagglutination-inhibiting) antibodies against TBE virus in as many as 78% of cases. Antibodies against LIP and BHA viruses were also detectable in the sera of 16% and 9%, respectively, of these individuals. Populations of the ectoparasites examined for the presence of arbovirus comprised 231 Ixodes ricinus, 806 Dermacentor marginatus and 204 Haemaphysalis punctata ticks and 117 specimens of the louse-flies Melophagus ovinus. Two strains of arbivirus that were antigenically related to Lipovník and Tribec viruses belonging to a group of Kemerovo viruses were isolated from male and female I. ricinus ticks collected from cattle.
Keywords: viry klíšťové encefalitidy; senioři; Arboviruses; Phthiraptera; Mice, Inbred ICR; Ticks; ovce; mladiství; Czechoslovakia; Neutralization Tests; Middle Aged; Československo; mužské pohlaví; Antibodies, Viral; Mice; Adult; skot; Encephalitis Viruses, Tick-Borne; Hemagglutination Inhibition Tests; dítě; testy inhibice hemaglutinace; Child; věkové faktory; ženské pohlaví; zvířata; Humans; myši inbrední ICR; klíšťata; Cattle; lidé středního věku; protilátky virové; myši; Age Factors; neutralizační testy; Goats; Sheep; dospělí; Female; arboviry; Aged; Adolescent; lidé; Male; kozy; Animals